Estimating the prevalence of gonococcal resistance to antimicrobials in England and Wales. Issue 6 (13th September 2011) - Hughes, Gwenda; Nichols, Tom; Ison, Catherine A
Abstract : Background: Gonorrhoea can rapidly develop resistance to antimicrobials and treatment options are becoming depleted. Treatment guidelines require robust estimates of the prevalence of resistance but sentinel surveillance systems may not be representative nationally. Objective: To investigate the effectiveness of the sentinel Gonococcal Resistance to Antimicrobials Surveillance System (GRASP) at estimating resistance prevalence in England and Wales. Methods: Annual cross-sectional data on reported gonorrhoea diagnoses between 2000 and 2008 were compared between GRASP (26 clinics) and national mandatory (KC60) reporting (229 clinics). Resistance prevalence estimates in GRASP were weighted according to the national distribution of relevant patient characteristics: age group, gender, sexual orientation and geographical region. Trends in actual and weighted estimates were plotted. Results: Gonorrhoea cases reported through GRASP were more likely to be from London and to be men who have sex with men (MSM) and were less likely to be women and heterosexual men than those reported through KC60. Weighting for national distributions of demographic characteristics reduced estimates of resistance prevalence, particularly ciprofloxacin in 2006 (27% to 21%). Emerging resistance to cefixime in 2008 was reduced from 1.5% to 1.0%. Weighting did not adjust resistance prevalence above or below the 5% threshold for any antimicrobial. Conclusions: Although over-representing MSM and under-representing women and heterosexual men, GRASP has provided reliable estimates of resistance prevalence in England and Wales. However, weighting for the national distribution of patient characteristics should be considered in future. As resistance usually emerges in MSM, enhanced surveillance of high-risk populations could enable development of more tailored (and therefore optimal) treatment strategies.